Pengaruh Sales Growth, Capital Intensity dan Leverage Terhadap Tax Avoidance Pada Perusahaan Sektor Energi Di Bursa Efek Indonesia - Kartika Tari; Hengky Leon (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Tax avoidance practices carried out within companies are a business strategy used to minimize the tax burden that companies will pay on their economic activities. Almost all companies that conduct business activities implement tax avoidance practices so that their net profits remain maximized without harming the company itself, by exploiting loopholes in the laws and regulations applicable in the country. Sales growth, capital intensity, and leverage are some of the factors that cause high tax rates to be imposed on company operations. Therefore, this study was conducted by limiting the scope of the research object, namely using 44 sample units of energy sector companies on the Indonesia Stock Exchange and 132 company research data, which were combined observations from 3 consecutive years in the period 2022 to 2024, using purposive sampling. Thus, the results of the study show that partially, sales growth and capital intensity do not affect tax avoidance, while leverage has a positive effect on tax avoidance. The potential of independent variables, namely sales growth, capital intensity, and leverage, in explaining the effect on tax avoidance is 39.2 percent, while the other 60.8 percent is influenced by other variables outside the research model.